(untitled) - Mcdougall, William (Cambridge, 1921)
1920. From the Preface: In this book I have sketched the principles of the mental life of groups, and have made a rough attempt to apply these principles to the understanding of the life of nations...I wish to make it clear to any would-be reader of this volume that it is a sequel to my Introduction to Social Psychology, that it builds upon that book and assumes that the reader is acquainted with it.
Keywords: Ethnopsychology,Social psychology,National characteristics